ANALISIS DAMPAK PENGGEMBALAAN SAPI DI TPA (Studi Kasus di TPA Piyungan – Yogjakarta - Wahyono, Sri (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The end of municipal solid waste operations is landfill. Almost all of the Indonesia cityÃ¢â‚¬â„¢sÃ‚Â landfills use the open dumping system. Generally, wastes dumped in the landfill areÃ‚Â dominated by organic materials that potentially used for cow feeding. So that, in someÃ‚Â landfills there are cow pasturing with the low cost operation related to the free feedingÃ‚Â materials. According to UU No 18/2008, in the year of 2013 open dumping landfill isÃ‚Â prohibited operate changed by sanitary landfill. Related to this change, the cow pasturingin landfill will be affected. So that the cow pasturing in landfill need to be assessed in theÃ‚Â aspect of waste reduction, economic values, landfill operation, social conflict, and safetyÃ‚Â cow meat. The goals of this study are assessing positive and negative impacts from cowÃ‚Â pasturing in the Piyungan Landfill, Yogjakarta. Research methods used are referencesÃ‚Â study, interview, counting the cow and direct investigation of landfill operation. ThisÃ‚Â study concluded that cow pasturing in landfill has positive impacts for waste reductionand increasing economic level of people live in surrounds of landfill. Unfortunately, theÃ‚Â cow pasturing has also negative impact such as disturbing daily landfill operation, highÃ‚Â potent social conflict during landfill rehabilitation, and high content of some heavy metalsÃ‚Â in the cow organ. Based on those impacts, the policy of the cow pasturing has to beÃ‚Â reviewed because of the importance of sanitary landfill operation in the near future andthe issue of safely consuming meat free from heavy metals.Key Words: landfill, waste, cow pasturing